Differential effects of metformin on breast cancer proliferation according to markers of insulin resistance and tumor subtype in a randomized presurgical trial - DeCensi, Andrea (Springer US, 2014)
Treatment of diabetics with metformin is associated with decreased breast cancer risk in observational studies, but it remains unclear if this drug has clinical antineoplastic activity. In a recent presurgical trial, we found a heterogeneous effect of metformin on breast cancer proliferation (ki-67) depending upon insulin resistance (HOMA index). Here, we determined the associations of additional serum biomarkers of insulin resistance, tumor subtype, and drug concentration with ki-67 response to metformin. Two-hundred non-diabetic women were randomly allocated to metformin (850 mg/bid) or placebo for 4 weeks prior to breast cancer surgery. The ki-67 response to metformin was assessed comparing data obtained from baseline biopsy (ki-67 and tumor subtype) and serum markers (HOMA index, C-peptide, IGF-I, IGFBP-1, IGFBP-3, free IGF-I, hs-CRP, adiponectin) with the same measurements at definitive surgery. For patients with a blood sample taken within 24 h from last drug intake, metformin level was measured. Compared with placebo, metformin significantly decreased ki-67 in women with HOMA > 2.8, those in the lowest IGFBP-1 quintile, those in the highest IGFBP-3 quartile, those with low free IGF-I, those in the top hs-CRP tertile, and those with HER2-positive tumors. In women with HOMA index > 2.8, drug levels were positively correlated with the ki-67 decrease, whereas no trend was noted in women with HOMA < 2.8 (p-interaction = 0.07). At conventional antidiabetic doses, the effect of metformin on tumor ki-67 of non-diabetic breast cancer patients varies with host and tumor characteristics. These findings are relevant to design breast cancer prevention and treatment trials with metformin. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10549-014-3141-1) contains supplementary material, which is available to authorized users.